Unraveling Resistance: The Teacher’s Dilemma with Distance Learning Platforms - Righi, Héla (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2024)
This paper presents the results of an exploratory study that was conducted among teachers at the Higher Institutes of Technological Studies in Tunisia on how they resisted the use of distance learning platforms. Different forms of resistance were expressed by participants, ranging from apathy to aggressive resistance. Several causes were revealed to justify this behaviour. The study showed that such resistance is multi-faceted and multi-dimensional, resulting in a multitude of practices that could be implemented to reduce teachers’ resistance.